Highly Active Sb-V-CeO2/TiO2 Catalyst Under Low Sulfur for NH3-SCR at Low Temperature - Jeong, Young Eun; Kumar, Pullur Anil; Ha, Heon Phil; Lee, Kwan-young (SPRINGER, 2017)
The Cu based zeolite NH3-SCR catalysts are well-known for after treatment of exhaust gases from light-and heavy-duty diesel engines. However, these catalysts are easily deactivated under the co-presence of H2O and SO2. In the present study, Sb-V-CeO2/TiO2 catalyst showed superior conversion for the abatement of NOx with NH3 under H2O and SO2 condition compared to commercial Cu-SAPO-34 and CuFe-ZSM-5 zeolite catalysts. The physico-chemical properties of fresh and used catalysts were examined by BET surface area, TEM (Transition electron microscopy) with EDS/EDX (Energy dispersive spectrometer/X-ray), XPS (X-ray photoelectron spectroscopy), DRIFTS (in situ diffuse reflectance infrared Fourier transformed spectroscopy) and H-2-TPR (temperature programmed reduction). Higher than 95% of initial NOx conversion was obtained over Sb-V-CeO2/TiO2 catalyst at 250 A degrees C under 14% H2O and 50 ppm SO2 conditions. The SO2 on/off test of the CuFe-ZSM-5 and Cu-SAPO-34 catalysts indicated a drastic decrease of NOx conversion when SO2 was turned on. In contrast, Sb-V-CeO2/TiO2 catalyst maintained a high NOx conversion and initial NOx conversion was completely recovered when SO2 was turned off. [GRAPHICS] .
Keywords: V2O5/WO3-TIO2 SCR CATALYSTS; NITRIC-OXIDE; NO REDUCTION; NH3; AMMONIA; SO2; ADSORPTION; UREA; CU; DEACTIVATION